REPRESENTASI KEKERASAN DAN DISKRIMINASI RAS DALAM FILM PENGEPUNGAN DI BUKIT DURI - Syifa Nadia; Iin Soraya; Yogi Ariska (CV Edujavare Publishing, 2025)
This study aims to analyze the representation of youth violence and racial discrimination in the film Pengepungan di Bukit Duri (2025) using Charles Sanders Peirce’s semiotic approach. The film highlights complex social issues such as juvenile delinquency, marginalization, and structural violence against the Chinese ethnic minority in Indonesia. Using a descriptive qualitative method, this research identifies and interprets visual signs, dialogues, and narratives that signify violence and discrimination. The findings show that the film represents social disintegration through symbols of physical violence, psychological pressure, and social injustice toward minority groups. This research is expected to contribute to academic discourse in visual communication studies and raise social awareness of discrimination and violence in media.